Visualizing collaborative time-varying scientific datasets - Mohamad Sharif, Johan (Springer Berlin Heidelberg, 2007)
Our perceptive of the scientific datasets has largely relied on numerical and statistical analysis of data from experimental dimension and computer simulation result [4][14][11][12][13]. In particular, we consider a simulated 3D time-varying model of scientific datasets and examine the temporal correlation among datasets. Our goal is to contrive effective visual representations to assist scientists in ascertaining temporal correlation among intricate and apparently chaotic scientific datasets. We propose a hybrid application with combination of streamline, global and local color scale and opacity scheme for spatio-temporal collaborative depiction. We illustrated also few images that can offer an effective tool for visually mining 3D time-varying scientific datasets.